Media Pembelajaran Berbasis Augmented Reality pada Mata Kuliah Mesin – Mesin Listrik - Goani Marind; Riki Mukhaiyar (Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to produce effective Augmented Reality-based learning media in the electrical machinery course in the Department of Electrical Engineering, Padang State University. The research method used is the method of research using the pre-Experimental research method with a One-Shot Case Study design. This type of One-Shot Case Study aims to see the power of measurement and the scientific value of a research design. In this method the application is made using supporting software, namely the Unity 2018 software, Android studio and Vuforia. Furthermore, the authors see whether the application that the author makes is feasible and effective to use as a learning medium through a questionnaire that will be provided and tested for validity. In its application, this learning media is applied to twenty-two students who are taking the Electrical Machines course at the Department of Electrical Engineering, Padang State University in 2022. Testing the feasibility of research materials obtained a figure of ninety-five percent for the feasibility test of the content of the material and ninety-five percent three percent for the media feasibility test where the figure shows that the learning media made are said to be very feasible to be used as research material. The implementation of the research shows that the use of Augmented Reality-based learning media in the Electrical Machines course can improve the quality of the learning process and student learning motivation. Based on data analysis, the average value of the effectiveness of learning media is seventy-point fifty six percent where this value can be categorized as effective as an alternative interactive learning media.